Lactobacillus Rhamnosus CRL1505 and its postbiotic improve emergency myelopoiesis against respiratory infection in immunosuppressed host - Vasile, Brenda Estefania (2021)
Emergency myelopoiesis is critical to control infection with pathogens. Patients undergoing chemotherapy have an impairment in hematopoiesis associated with an ineffective immune response against infections. Lactobacillus rhamnosus CRL1505 (Lr05) and its cell wall (CW05) diet supplementation has proved to be an interesting alternative to improve steady-state myelopoiesis. In this work we studied the effect of oral administration of Lr05 and CW05 on the emergency myelopoiesis induced by TLR4 agonist in immunosuppressed mice. Adult Swiss-mice were orally treated with Lr05 or CW05 during 10 consecutive days. On day 6, treated and untreated mice received one intraperitoneal dose of cyclophosphamide (Cy 150mg/kg). On day 3 post-Cy injection, mice were challenged intraperitoneal with LPS (10mg/kg weight). At different post-challenge times, the following studies were carried out: 1) recruitment of phagocytic cells(neutrophils and macrophages) in peritoneal lavage; 2) frequency of hematopoietic stem cells (HSCs) (Lin-Sca-1+c-Kit+), and myeloid multipotent precursors (MMPs) (Lin-Sca-1+c-Kit+CD34+) in BM and; 3) release of neutrophils from myelopoietic niches by the expression of CXCR4 and CD62L in BM Gr-1+Ly6G+Ly6C- cells. The Cy group showed an impaired local innate immune response, a decrease of HSCs and MMPs, and an anchoring of myeloid precursors in BM. However, Lr05 and CW05 treatments were effective to significantly increase peritoneal neutrophils and macrophages and allow an early HSCs and MMPs recovery with respect to the Cy group. These results were correlated with a decrease in the retention signals in the BM cells of Lr05 or CW05 groups compared to the Cy control. In conclusion, the postbiotic obtained from L. rhamnosus CRL1505 is capable of modulating a more efficient local innate immune response. This in turn could be correlated with the modulation of chemokines responsible for stimulating an adequate emergency myelopoietic response in BM against the pathogen.